2014
DOI: 10.1515/ract-2013-2203
|View full text |Cite
|
Sign up to set email alerts
|

Studies on U-Zr and U-Pu-Zr alloys for determination of Cl and F using pyrohydrolysis

Abstract: Pyrohydrolysis method was studied for the separation of Cl and F from U-Zr and U-Pu-Zr alloy nuclear fuels and determination by ion chromatography. A detailed study was performed on pyrohydrolysed products of U-Zr alloy, obtained on heating in moist argon and oxygen atmospheres using X-ray powder diffraction (XRD) and thermogravimtric methods. Using oxygen as the carrier gas pyrohydrolysis performed at 900 ∘ C was complete within 30 min. It was found that, moist oxygen as carrier gas only could open the matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study also showed in addition to the pyrohydrolisability, the matrix opening is also a crucial factor for achieving the complete recovery of halogens. 52 An ion chromatographic study deals with the separation and identification of pyrohydrolysis products of (U, Pu) C has been reported 53 and the study further reported that the pyrohydrolytic conditions are responsible for the formation of organic acids during the pyrohydrolysis of metal carbides. Another study reports about the pyrohydrolytic separation of boron in U 3 Si 2 required for the determination of isotopic composition of boron by ICP-MS. 54 Pyrohydrolysis was used for generation of zirconia from ZrF 4 .…”
Section: Pyrohydrolysis In Nuclear Industrymentioning
confidence: 99%
“…The study also showed in addition to the pyrohydrolisability, the matrix opening is also a crucial factor for achieving the complete recovery of halogens. 52 An ion chromatographic study deals with the separation and identification of pyrohydrolysis products of (U, Pu) C has been reported 53 and the study further reported that the pyrohydrolytic conditions are responsible for the formation of organic acids during the pyrohydrolysis of metal carbides. Another study reports about the pyrohydrolytic separation of boron in U 3 Si 2 required for the determination of isotopic composition of boron by ICP-MS. 54 Pyrohydrolysis was used for generation of zirconia from ZrF 4 .…”
Section: Pyrohydrolysis In Nuclear Industrymentioning
confidence: 99%